Determinants of Technical Efficiency of Cocoa Farmers in Malaysia - Wan Roshidah Fadzim; Mukhriz Izraf Azman Aziz; Ahmad Zafarullah Abdul Jalil (International Journal of Supply Chain Management, 2017)
The study of the determinants of technical efficiency among smallholder cocoa farmers has been well studied and still attracts more studies in the agricultural literature. Among the factors attract attention are the demographic characteristics that affect farmers decision-making process and the ability of farmers to execute the decision effectively. Cocoa production in Malaysia faces a multiplicity of problems which results into low productivity, thus leading a continuous fall in percentage share of cocoa output since 2001. Currently, no study has focussed on the investigation of this issue from the supply perspective. This study will deal with the determinants of technical efficiency among cocoa farmers in Malaysia during the year 2013 production season using the Tobit estimator. Questionnaires were administered to 323 smallholder cocoa farmers throughout Malaysia and data were collected. The results of the analysis showed that ratio, number of clones, record keeping, status of farmers (either part-time or full-time basis), knowledge, farming course and plant location affects efficiency. This finding suggests that policies that would directly affect these identified variables be pursued.